Special Issue “Exercise and Neurodegenerative Disease 2.0” - Grazia Maugeri; Velia D’Agata (Journal of Functional Morphology and Kinesiology)
It is well known that sedentary life is detrimental for human health; on the contrary, an active lifestyle represents an efficient instrument to guarantee and promote physical and psychological health [...]